2018
DOI: 10.1002/eqe.3058
|View full text |Cite
|
Sign up to set email alerts
|

Rocking amplification and strong‐motion duration

Abstract: Summary This paper characterizes the ability of natural ground motions to induce rocking demands on rigid structures. In particular, focusing on rocking blocks of different size and slenderness subjected to a large number of historic earthquake records, the study unveils the predominant importance of the strong‐motion duration to rocking amplification (ie, peak rocking response without overturning). It proposes original dimensionless intensity measures (IMs), which capture the total duration (or total impulse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
106
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 65 publications
(112 citation statements)
references
References 67 publications
5
106
1
Order By: Relevance
“…A relatively more challenging task lies in the prediction of overturning probability P (O|U). Using multiple stripe analysis together with the maximum likelihood concept, previous studies have identified that the overturning probability of rigid rocking structures can be reasonably predicted when it is conditioned on the dimensionless IM of fritalicPGVgtanα . This study utilizes a different approach, ie, the machine learning framework with the logistic regression method, but also identifies that ln()fitalicrPGVgtanα is the best predictor among various parameters.…”
Section: Conditional Probability Damage Models Of the Rocking Bridgesmentioning
confidence: 99%
See 3 more Smart Citations
“…A relatively more challenging task lies in the prediction of overturning probability P (O|U). Using multiple stripe analysis together with the maximum likelihood concept, previous studies have identified that the overturning probability of rigid rocking structures can be reasonably predicted when it is conditioned on the dimensionless IM of fritalicPGVgtanα . This study utilizes a different approach, ie, the machine learning framework with the logistic regression method, but also identifies that ln()fitalicrPGVgtanα is the best predictor among various parameters.…”
Section: Conditional Probability Damage Models Of the Rocking Bridgesmentioning
confidence: 99%
“…The prediction of rocking uplift responses is of the main interest of recent studies that investigate the dynamics of rocking structures . In these studies, various ground motion IMs have been compared in terms of their efficiency and sufficiency to correlate to the rocking uplift demand.…”
Section: Conditional Probability Damage Models Of the Rocking Bridgesmentioning
confidence: 99%
See 2 more Smart Citations
“…Since then, a plethora of papers on rocking structures has been published studying these structures theoretically [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and experimentally. Their systematic study started after the 1960 Chilean earthquake, when Housner published his seminal paper 1 on the behavior of "inverted pendulum structures."…”
Section: Introductionmentioning
confidence: 99%